A note on generalized derivations on prime rings

Arabian Journal of Mathematics, Dec 2017

Let R be a prime ring with the extended centroid C and symmetric Martindale quotient ring \(Q_s(R)\). In this paper we prove the following result. Let \(F: R \rightarrow R\) be a generalized derivation associated with a non-zero derivation d on R and let h be an additive map of R such that \(F(x)x=xh(x)\) for all \(x\in R\). Then either R is commutative or \(F(x)=xp\) and \(h(x)=px\) where \(p\in Q_{s}(R)\).

A PDF file should load here. If you do not see its contents the file may be temporarily unavailable at the journal website or you do not have a PDF plug-in installed and enabled in your browser.

Alternatively, you can download the file locally and open with any standalone PDF reader:

https://link.springer.com/content/pdf/10.1007%2Fs40065-017-0193-1.pdf

A note on generalized derivations on prime rings

A note on generalized derivations on prime rings Maja Fošner 0 Nadeem ur Rehman 0 Tarannum Bano 0 Mathematics Subject Classification 0 0 N. ur Rehman Let R be a prime ring with the extended centroid C and symmetric Martindale quotient ring Qs ( R). In this paper we prove the following result. Let F : R → R be a generalized derivation associated with a non-zero derivation d on R and let h be an additive map of R such that F (x )x = x h(x ) for all x ∈ R. Then either R is commutative or F (x ) = x p and h(x ) = px where p ∈ Qs ( R). Throughout the paper, R will be an associative ring with center Z . Recall that R is prime if for any a, b ∈ R, a Rb = 0 implies that a = 0 or b = 0. By Ql ( R) and Qr ( R) we denote the left Martindale ring of quotients of R and the right Martindale ring of quotients of R, respectively. Further, we denote by Qs ( R) the symmetric Martindale quotients ring of ring R. The center C of Qs ( R) is a field and it is the center of both Ql ( R) and Qr ( R). It is called the extended centroid of R. Also it is easily seen that C is the centralizer of R in both Qr ( R) and Ql ( R). In particular, Z ⊆ C . The subring of Qr ( R) (or Ql ( R)) generated by R and C is called the central closure of R and will be denoted by RC . Another subring of Qr ( R) is Qs ( R) = {q ∈ Qr |I q ⊆ R - 1 Introduction for some nonzero ideal I of R}. It is called the symmetric Martindale ring of quotients. We point out that R ⊆ RC ⊆ Qs (R) ⊆ Qr (R). Note that q1 Rq2 = 0, where q1, q2 ∈ Ql (R) or q1, q2 ∈ Qr (R) implies that q1 = 0 or q2 = 0. In particular, this shows that all RC , Qs (R), Ql (R), and Qr (R) are prime rings, so that one can construct (left, right, symmetric) Martindale ring of quotients and the central closure of each of these rings. Let RC ∗C C {X } be the free product over C of RC and the free algebra over C on an infinite set X of indeterminates. A typical element in RC ∗C C {X } is a sum of monomials of the form λai0 x j1 ai1 x j2 . . . x jn ain where λ ∈ C, aik ∈ RC and x jk ∈ X . R satisfy a generalized polynomial identity over C (simply R is a GPI ring) if there exists a nonzero polynomial p(x1, x2, . . . , xn) ∈ RC ∗C C {X } such that p(r1, r2, . . . , rn ) = 0 for all r1, r2, . . . , rn ∈ R. We refer the reader to [2,3] for more details. An additive map d : R → R is called a derivation if d(x y) = d(x )y + x d(y) holds for all x , y ∈ R. In particular, for a fixed a ∈ R, the map Ia : R → R given by Ia (x ) = [x , a] is a derivation called an inner derivation. Let S be a non-empty subset of R. A map f : R → R is said to be centralizing on S if [ f (x ), x ] ∈ Z for every x ∈ S. In special case where [ f (x ), x ] = 0 for every x ∈ S, the map f is called commuting on S. The study of centralizing maps was initiated by a well-known theorem of Posner [15] which states that the existence of a nonzero centralizing derivation on a prime ring R implies that R is commutative. A number of authors have extended Posner’s theorem in several ways. They have showed that nonzero derivations cannot be centralizing on various subsets of noncommutative prime rings (see [12] for probably the most general results of the kind), and similar conclusion hold for some other maps. In [5] Brešar studied maps that are centralizing and additive, and no further assumption was required. The main result of [5] characterizes commuting additive maps on prime rings R: every such map is of the form x → λx + h(x ) where λ ∈ C , and h is an additive map of R into C . Later, Lanski [13] dealt with the situation where a nonzero derivation d of a prime ring R satisfies c1x d(y) + c2d(x )y + c3 yd(x ) + c4d(y)x ∈ C for some ci ∈ C and all x , y ∈ S, where S is a subset of R. Neglecting rings of characteristic 2, the conclusion was: either all ci = 0 or R satisfies S4, the standard identity of degree 4 (however, the exact statements are much more precise). The condition considered by Lanski clearly covers the case of centralizing derivations, namely a linearization of [d(x ), x ] ∈ Z gives x d(y)−d(x )y + yd(x )−d(y)x ∈ Z . The same is true for the case skew-centralizing on S if f (x )x +x f (x ) ∈ Z for all x ∈ S. In the special case where f (x )x + x f (x ) = 0 for all x ∈ S, the map f is called skew-commuting on S. In [6] Brešar proved that there is no nonzero additive maps that are skew-commuting on ideals of prime rings of characteristic not 2. An additive map F : R → R is called a generalized inner derivation if F (x ) = ax + x b for fixed a, b ∈ R. For such a map F , it is easy to see that F (x y) = F (x )y + x [y, b] = F (x )y + x Ib(y) for all x , y ∈ R. This observation leads to the following definition, given in [4] and [9]; an additive map F : R → R is called a generalized derivation with associated derivation d if F (x y) = F (x )y + x d(y) holds for all x , y ∈ R. Familiar examples of generalized derivations are derivations and generalized inner derivations and the later includes left multiplier, i.e., an additive map F : R −→ R satisfying F (x y) = F (x )y for all x , y ∈ R. In [11], Lee extended the definition of a generalized derivation as follows: by a generalized derivation we mean an additive mapping F : I → U such that F (x y) = F (x )y + x d(y) holds for all x , y ∈ I , where I is a dense left ideal of R, U is the Utumi quotient ring (i.e., the maximal right quotient ring) of R and d is a derivation from I to U . Moreover, Lee also proved that every generalized derivation can be uniquely extended to a generalized derivation of U , and thus all generalized derivations of R will implicitly assumed to be defined on the whole of U . Lee obtained the following: every generalized derivation F on a dense left ideal of R can be extended to U and assumes the form F (x ) = ax + d(x ) for some a ∈ U and a derivation d on U . Motivated by the work of Brešar [5] and Lanski [13], in this paper we consider F as a generalized derivation and h as an additive map of R such that F (x )x = x h(x ) for all x ∈ R. In fact, our result extends Posner’s Theorem [15], Brešar’s Theorem [5] and Ashraf et al. [1]. 2 Main result In this section we shall prove our main theorem. Before that we need some known results: Lemma 2.1 [14, Theorem 3] A prime ring R satisfies a GPI if and only if RC is a primitive ring with nonzero socle and e RC e is a finite-dimensional division algebra over C for each primitive idempotent e in RC . Lemma 2.2 [7, Main Theorem] Let R be prime ring and let n, m, k, l be positive integers. Suppose that in=1 Fi (y)x ai + m i=1Gi (x )ybi + ik=1ci y Hi (x ) + l i=1di x Ki (y) = 0 for all x, y ∈ R, where Fi , Gi , Hi , Ki : R → RC are additive maps and {a1, . . . , an}, {b1, . . . , bm}, {c1, . . . , ck }, {d1, . . . , dl } are C-independent subsets of R. Then one of the two possibilities holds: (i) RC is a primitive ring with nonzero socle and e RC e is a finite-dimensional division algebra over C for each primitive idempotent e in RC ( that is, R is a GPI ring), (ii) There exists elements qi j ∈ Qs (RC ), i = 1, . . . , l, j = 1, . . . , m, pi j ∈ Qs (RC ), i = 1, . . . , k, j = 1, . . . , n and additive maps λi j : R → C, i = 1, . . . , l, j = 1, . . . , n, μi j : R → C, i = 1, . . . , m, j = 1, . . . , k, such that Fi (y) = kj=1c j yp ji + lj=1λ ji (y)d j , for all y ∈ R, i = 1, . . . , n, Gi (x) = lj=1d j xq ji − kj=1μi j (x)c j , for all x ∈ R, i = 1, . . . , m, Hi (x) = − nj=1 pi j xa j + mj=1μ ji (x)b j , for all x ∈ R, i = 1, . . . , k, Ki (y) = − mj=1qi j yb j − lj=1λ ji (y)a j , for all y ∈ R, i = 1, . . . , l. Lemma 2.3 [10, Theorem 2] Let R be a prime ring, U its maximal right quotient ring and IR a dense R-submodule of UR. Then I and U satisfy the same differential identities Now we are well equipped to prove our theorem: Theorem 2.4 Let R be a prime ring and F : R → R be a generalized derivation associated with a non-zero derivation d. Further let h be an additive map of R such that F(x)x = x h(x) for all x ∈ R. Then either R is commutative or F(x) = x p and h(x) = px where p ∈ U . Proof We have F(x)x = x h(x) for all x ∈ R. Linearizing this relation we have F(y)x + F(x)y − yh(x) − x h(y) = 0 for all x, y ∈ R. We solve this functional identity in two different cases. Case I: R is not a GPI ring. Using Lemma 2.2, we get from ( 1 ) where λ, μ : R → C additive maps. From ( 2 ), we have F(y) − yp = λ(y) ∈ C. Let G be the additive map defined as G(y) = F(y) − yp for any element y ∈ R. Since F is a generalized derivation with associated derivation d, first we prove that G is a generalized derivation of R. G(x y) = F(x y) − x yp = F(x)y + xd(y) − x yp = F(x)y + xd(y) − x yp + (x py − x py) = (F(x) − x p)y + x(d(y) + [ p, y]) = G(x)y + xg(y), where g(x) = d(x) + [ p, x] is the associated derivation of G. Hence G is a generalized derivation. Thus, by ( 2 ) G(y) is central in R, for any element y ∈ R. Hence by Hvala [9, Lemma 3] either R is commutative or G = 0, which imply F(y) − yp = 0 and hence F(y) = yp for any y ∈ R. Similarly from ( 3 ), we find that either R is commutative or F(x) = xq. These two relations imply that p = q and λ = μ = 0 and hence h(x) = px where p ∈ U . Case II: R is a GPI ring. If there exists a nonzero idempotent e in RC . If there exists e2 = e = {0, 1} in Qs (R). Therefore, we can find a nonzero ideal I of R satisfying eI + I e ⊆ R. Then from ( 1 ), we get F(ey)ex + F(ex)ey = ex h(ey) + eyh(ex), for all x, y ∈ I. Thus F(ey)ex + F(ex)ey = e{F(ey)ex + F(ex)ey}, for all x, y ∈ I. F(y) = yp + λ(y), F(x) = xq + μ(x), h(x) = px + μ(x), h(y) = q y + λ(y), ( 1 ) ( 2 ) ( 3 ) ( 4 ) ( 5 ) ( 6 ) ( 7 ) ( 8 ) ( 9 ) ( 10 ) ( 11 ) This implies that By Lemma 2.3, Qs (R) and I satisfy the same differential identity. Thus we have (1 − e)F (ey)ex + (1 − e)F (ex )ey = 0, for all x , y ∈ I. (1 − e)F (ey)ex + (1 − e)F (ex )ey = 0, for all x , y ∈ Qs (R). where H (x ) = (1 − e)F (ex )e. Replacing x by x z in ( 6 ), we get Multiplying ( 6 ) by z from the right, we find that Comparing ( 7 ) and ( 8 ), we find that Replacing y by yu in ( 9 ), we get Right multiplication of ( 9 ) by u, we get H (x )y + H (y)x = 0, H (x z)y + H (y)x z = 0. H (x )yz + H (y)x z = 0. H (x z)y = H (x )yz. H (x z)yu = H (x )yuz. H (x z)yu = H (x )yzu. Comparing ( 10 ) and ( 11 ), we get H (x )y[z, u] = 0 for all x , y, z, u ∈ Qs (R). Since R is prime and Qs (R) is also prime, we get from the last relation either R is commutative or H (x ) = 0 for all x ∈ Qs (R). If H (x ) = 0, we get (1 − e)F (ex )e = 0 and considering F (x ) = ax + d(x ) for a ∈ U , we find that This implies (1 − e)[aex + d(ex )]e = 0. (1 − e)aex e + (1 − e)d(e)x e = 0. Let x y−1 = u in ( 12 ), we get Since R is prime and e is non-trivial, we get (1 − e)ae + (1 − e)d(e) = 0 for all non-trivial idempotents e ∈ Qs (R). Replacing e by 1 − e we get ea(1 − e) + ed(−e) = 0. Combining these two relations we get d(e)+[a, e] = 0. Let E be an additive subgroup generated by idempotents in Qs (R). Therefore, d(u)+[a, u] = 0 for all u ∈ E . Now, for all u, v ∈ E , we get d(uv) + [a, uv] = 0 = (d(u) + [a, u])v + u(d(v) + [a, v]). That is, d(u) + [a, u] = 0 for all u ∈ E = [E , E ]. Now [E , E ] = 0, since [e, e + ex (1 − e)] = 0 for some x ∈ Qs (R). By Herstein’s arguments [8, page 4] 0 = Qs [E , E ]Qs ⊆ E , W = Qs [E , E ]Qs is a nonzero ideal of Qs . Therefore, d(u) + [a, u] = 0 for all u ∈ W and hence d(x ) + [a, x ] = 0 for all x ∈ Qs (R) by Lemma 2.3. Thus F (x ) = ax + d(x ) = ax − [a, x ] = x a. By Martindale’s theorem [14, Theorem 3] we know that RC is a primitive ring and H = soc(RC ) = 0 and e RC e is a finite dimensional for any minimal idempotent e. If H contains no non-trivial idempotent, then H is a finite-dimensional division algebra over C . If soc (RC ) contains no nontrivial idempotent, then soc (RC ) must be a finite-dimensional division algebra over C , by [14, Theorem 3]. Since soc (RC ) is a nonzero ideal of RC , it follows RC = soc (RC ) is a division algebra. Then for x = 0 ∈ R we have from the given condition h(x ) = x −1 F (x )x in RC . For any x , y = 0 ∈ R we get from ( 1 ) F (x )y + F (y)x = x y−1 F (y)y + yx −1 F (x )x . ( 12 ) F (uy)y + F (y)uy = u F (y)y + u−1 F (uy)uy for all u, y(= 0) ∈ R, and this implies that u F (u y)y + u F (y)u y = u2 F (y)y + F (u y)u y for all 0 = u, y ∈ R. u F (u y) + u F (y)u = u2 F (y) + F (u y)u for all u, y ∈ R. Since F (x ) = ax + d (x ) for a ∈ Qs ( R), we get from the last relation uau y + ud (u y) + uayu + ud (y)u = u2ay + u2d (y) + au yu + d (u y)u. The above relation for y = 1 gives us uau + ud (u) + uau = u2a + au2 + d (u)u. This implies that [u, d (u)] = [u, [u, a]], hence d (u) = [u, a]; now we get F (x ) = ax + x a − ax = x a and by our assumption that F (x )x = x h(x ), we get h(x ) = ax , which completes the proof. Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http:// creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations. 1. Ashraf , M. ; Rehman , N. ; Ali , S. ; Mozumder, M.R. : On semiprime rings with generalized derivations . Bol. Soc. Parana de Mat . 28 , 15 - 22 ( 2010 ) 2. Beidar , K.I. ; Brešar, M. ; Chebotar , M.A. : Functional identities revisited: the functional and the strong degree . Commun. Algebra 30 , 935 - 969 ( 2002 ) 3. Beidar , K.I. ; Martindale III , W.S.; Mikhalev , A.V. : Rings with Generalized Identities , Monographs and Textbooks in Pure and Applied Mathematics , vol. 196 . Marcel Dekker , Inc., New York ( 1996 ) 4. Brešar , M. : On the distance of the composition of two derivations to the generalized derivations . Glasgow Math. J. 33 , 89 - 93 ( 1991 ) 5. Brešar , M. : Centralizing mappings and derivations in prime rings . J. Algebra 156 , 385 - 394 ( 1993 ) 6. Brešar , M. : On skew-commuting mappings of rings . Bull. Aust. Math. Soc . 47 , 291 - 296 ( 1993 ) 7. Brešar , M.: Functional identities of degree two . J. Algebra 172 , 690 - 720 ( 1995 ) 8. Herstein , I.N.: Topics in Ring Theory . University of Chicago Press, Chicago ( 1969 ) 9. Hvala , B. : Generalized derivations in rings . Commun. Algebra 26 , 1147 - 1166 ( 1998 ) 10. Lee , T.K. : Semiprime rings with differential identities . Bull. Inst. Math. Acad. Sinica 20 ( 1 ), 27 - 38 ( 1992 ) 11. Lee , T.K. : Generalized derivations of left faithful rings . Commun. Algebra 27 ( 8 ), 4057 - 4073 ( 1999 ) 12. Lanski , C. : Differental identities, Lie ideals, and Posner's theorems . Pac. J. Math. 134 , 275 - 297 ( 1988 ) 13. Lanski , C. : Lie ideals and central identities with derivation . Can. J. Math. 44 , 553 - 560 ( 1992 ) 14. Martindale III , W.S.: Prime rings satisfying a generalized polynomial identity . J. Algebra 12 , 576 - 584 ( 1969 ) 15. Posner , E.C. : Derivations in prime rings . Proc. Am. Math. Soc. 8 , 1093 - 1100 ( 1957 )


This is a preview of a remote PDF: https://link.springer.com/content/pdf/10.1007%2Fs40065-017-0193-1.pdf

Maja Fošner, Nadeem ur Rehman, Tarannum Bano. A note on generalized derivations on prime rings, Arabian Journal of Mathematics, 2017, 1-5, DOI: 10.1007/s40065-017-0193-1